2013
DOI: 10.3390/ma6041485
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Microstructure of Class C Fly Ash-Based Geopolymer Paste and Mortar

Abstract: This paper presents workability, compressive strength and microstructure for geopolymer pastes and mortars made of class C fly ash at mass ratios of water-to-fly ash from 0.30 to 0.35. Fluidity was in the range of 145–173 mm for pastes and 131–136 mm for mortars. The highest strengths of paste and mortar were 58 MPa and 85 MPa when they were cured at 70 °C for 24 h. In XRD patterns, unreacted quartz and some reacted product were observed. SEM examination indicated that reacted product has formed and covered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 31 publications
(48 reference statements)
3
36
0
Order By: Relevance
“…Many studies have shown that hardening slows down due to FA replacement [30,33,34]. In the previous work, it was thought that calcium in fly ash would act as a contaminant, creating hydrate assemblages that would reduce mechanical strength and slow down the reaction rate [35]. SF6 has the highest compressive strength as compared to other binary mixes of SF, a decline happens in the compressive strength of binary mixes of SF, as the replacement ratio of SF increases in binary mixes of SF, this decrease is not as much as that occurs in binary mixes of FA.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Many studies have shown that hardening slows down due to FA replacement [30,33,34]. In the previous work, it was thought that calcium in fly ash would act as a contaminant, creating hydrate assemblages that would reduce mechanical strength and slow down the reaction rate [35]. SF6 has the highest compressive strength as compared to other binary mixes of SF, a decline happens in the compressive strength of binary mixes of SF, as the replacement ratio of SF increases in binary mixes of SF, this decrease is not as much as that occurs in binary mixes of FA.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…In fly ash based geopolymer concrete, the amount of water content usually defined by water to solid (fly ash) ratio or in some study expressed as H O to Na O ratio. It also has been shown to affect the workability of a mixture for both low calcium [43] and high calcium [17] fly ash based geopolymer concretes. This trend of water content affecting on the workability and later on compressive strength is the same with the conventional Portland cement concrete, where the chemical reaction involved is hydration process [44].…”
Section: Fresh State Behaviorsmentioning
confidence: 99%
“…Many researchers have been investigating about the chemistry [5,6,10], the reaction mechanism [6,7,11], the fresh and hardened properties [8,[12][13][14], the microstructure [15][16][17], and so much more, about this fly ash based geopolymers concrete. Although there are so many researches have been conducted, until now, there is still no clear and standardized guide about the making procedure of fly ash based geopolymer concrete, especially in terms of structural applications.…”
Section: Fly Ash Based Geopolymers Concretementioning
confidence: 99%
“…Microscopic images of the fly ash-based geopolymer prepared using FA1 and FA2 are shown in Figure 4.a and Figure 4.b, respectively. The SEM micrographs revealed that the amount of calcium leads to the formation of calcium silicates in addition to geopolymer gel products (Xueying at al., 2013) [19].…”
Section: Sem Analysismentioning
confidence: 99%